EFFECT OF SPEED READING METHOD ON THE STUDENTS ABILITY TO UNDERSTAND AN ESP TEXT - Lily, Lily (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research was quasy experiment research. This research was done in STIKes Sehat Medan during Nov – December 2023. The population of this research was the first semester students for D3 Nursing Program, 31 students, academic year 2023/2024. This research was conducted with the aim of finding out about speed reading, speed reading techniques, and especially knowing the effect of the speed reading on the students' ability to understand ESP text that is the English reading texts for nursing. Based on the analysis of data using t-test, it was found that the tcount > ttable, both using the speed reading, scanning technique, tcount (9,175) > ttable (2,042), and the speed reading skimming technique, tcount (7,628) > ttable (2,042), with significance level 0,005. The results of the research showed that there was an affect of the speed reading on the ability of the students to understand an ESP text, English Specific Purpose texts for nurses.